Endoscopic ultrasound hemostasis techniques - Artifon, Everson L.A. (2017)
Since its development, endoscopic ultrasound (EUS) has evolved from a simple diagnostic technique to an important therapeutic tool for interventional endoscopy. EUS analysis provides real-time imaging of most major thoracic and abdominal vessels, and the possibility to use needle puncture with a curved linear array echoendoscope as a vascular intervention. In this review, we describe the endoscopic ultrasound approach to vascular therapy outside of the gastrointestinal wall.